2014
DOI: 10.1039/c4ta05530f
|View full text |Cite
|
Sign up to set email alerts
|

SnTe–AgBiTe2 as an efficient thermoelectric material with low thermal conductivity

Abstract: SnTe is an intriguing alternative to its sister compound PbTe in thermoelectric energy conversion because of their electronic and structural similarity; however, it is challenging to optimize its thermoelectric performance to the level of PbTe because of the difficulties in decreasing its intrinsically large hole population and high thermal conductivity arising from the tin vacancies. We demonstrate here that by alloying some AgBiTe 2 in SnTe, thus forming AgSn x BiTe x+2 compositions the hole concentration ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
135
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 41 publications
16
135
1
1
Order By: Relevance
“…Introducing inclusions (especially for nanoinclusions acted as 3D lattice imperfections which have high interface density and nanoscale effects) can further reduce κ l by strengthening phonon scattering at the strain fields induced by these inclusions, the inducing of nanoinclusions is a good strategy to further lower κ and in turn enhance ZT, which can be simply realized by solution route 24. When there are nanoinclusions in SnSe matrix, we have100,253,254 κl=κlp tan1uu where κ lp is lattice thermal conductivity of parent sample (SnSe in this case). The parameter u is defined as100,253,254 u =π2θDnormalΩv2κlpnormalΓ12 where Ω is the volume per atom and Γ is imperfection‐scaling parameter100,253,254 Γ =normalΓM +εnormalΓS where Γ M is calculated by average sublattice mass and Γ S is calculated by average sublattice ionic radius.…”
Section: Fundamentalmentioning
confidence: 99%
“…Introducing inclusions (especially for nanoinclusions acted as 3D lattice imperfections which have high interface density and nanoscale effects) can further reduce κ l by strengthening phonon scattering at the strain fields induced by these inclusions, the inducing of nanoinclusions is a good strategy to further lower κ and in turn enhance ZT, which can be simply realized by solution route 24. When there are nanoinclusions in SnSe matrix, we have100,253,254 κl=κlp tan1uu where κ lp is lattice thermal conductivity of parent sample (SnSe in this case). The parameter u is defined as100,253,254 u =π2θDnormalΩv2κlpnormalΓ12 where Ω is the volume per atom and Γ is imperfection‐scaling parameter100,253,254 Γ =normalΓM +εnormalΓS where Γ M is calculated by average sublattice mass and Γ S is calculated by average sublattice ionic radius.…”
Section: Fundamentalmentioning
confidence: 99%
“…Tan et al reported a considerably improved S due to the convergence of two valence bands and the widening of band gap by doping with Hg and Cd, 17,18 and Zhang et al reported that indium alloying in SnTe could improve the electrical properties by inducing resonant levels inside the valence band. [20][21][22] Although some encouraging progress has been made on the improvement of TE performance of SnTe, noteworthily, some toxic or rare components like Cd, Hg, Pb, and Ag are still the main candidates for the dopants or the secondary phases introduced in the compound. [20][21][22] Although some encouraging progress has been made on the improvement of TE performance of SnTe, noteworthily, some toxic or rare components like Cd, Hg, Pb, and Ag are still the main candidates for the dopants or the secondary phases introduced in the compound.…”
Section: Introductionmentioning
confidence: 99%
“…19 Besides, some nanoparticles such as CdS, HgTe, and AgBiTe 2 , have also been introduced to reduce the thermal conductivity of SnTe compounds. [20][21][22] Although some encouraging progress has been made on the improvement of TE performance of SnTe, noteworthily, some toxic or rare components like Cd, Hg, Pb, and Ag are still the main candidates for the dopants or the secondary phases introduced in the compound.…”
Section: Introductionmentioning
confidence: 99%
“…And PbTe contain toxic elements such as Pb, which was restricted all over the world. Recently, as a result of deeper theoretical understanding 27,28 and imaginative experimental approaches, the thermoelectric performance of ptype SnTe has been much improved 26,[29][30][31][32] and the material has started to command considerable interest. SnTe-based compounds are narrow-band semiconductors 21,22 which crystallize in the NaCl type structure and are always high carrier concentration p-type semiconductors due to the high density of intrinsic cation vacancies 23 .…”
Section: Introductionmentioning
confidence: 99%